2022
DOI: 10.3389/fendo.2022.940309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of vascular complications in type 2 diabetes mellitus: Results from discover Middle East and Africa cohort

Abstract: BackgroundWe evaluated the prevalence of vascular complications and associated risk factors in individuals with type 2 diabetes mellitus (T2DM) initiating second-line glucose-lowering therapy from the Middle East and Africa (MEA) cohort of the 3-year prospective DISCOVER study involving 15,992 patients in 38 countries.MethodsBaseline cross-sectional data collected from healthcare settings were used to assess micro and macrovascular complications prevalence as crude and age- and sex-standardised. The multi‐vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Several studies conducted in Palestine have reported varying prevalence rates of microvascular complications, ranging from 39% to 67% [26,33] which is much higher than our study findings. The study rates in our research exhibit a lesser magnitude in comparison to those observed in Jordan, although they demonstrate a greater level when compared to other economically developed Arabic nations such as Kuwait and Bahrain [34]. In a similar manner, our observed prevalence exhibited a lesser magnitude when compared to Australia, Colombia, and Iran although it displayed a larger magnitude in relation to the studies conducted in Ireland [35].…”
Section: Prevalence Rates Of Diabetes-related Complicationssupporting
confidence: 47%
“…Several studies conducted in Palestine have reported varying prevalence rates of microvascular complications, ranging from 39% to 67% [26,33] which is much higher than our study findings. The study rates in our research exhibit a lesser magnitude in comparison to those observed in Jordan, although they demonstrate a greater level when compared to other economically developed Arabic nations such as Kuwait and Bahrain [34]. In a similar manner, our observed prevalence exhibited a lesser magnitude when compared to Australia, Colombia, and Iran although it displayed a larger magnitude in relation to the studies conducted in Ireland [35].…”
Section: Prevalence Rates Of Diabetes-related Complicationssupporting
confidence: 47%
“…However, the estimated prevalence of 28 million people with diabetes in Africa by 2030 predicts a higher incidence of diabetes complications in Africa, particularly with increased urbanization (which is associated with increased consumption of processed and highly salted and fatty foods, sedentary lifestyle, and poor physical activities) [46]. Diabetes has a reported prevalence of 12.2% in the Middle East and North Africa and 12.7% in South Africa in people aged 20 to 79 years old [47].…”
Section: Prevalence Of Diabetes Mellitus Macrovascular Complicationsmentioning
confidence: 99%
“…In another study conducted in Tianjin, China, the prevalence of microvascular complications was 34.5% [4]. A study conducted in the Middle East and Africa cohort found the overall crude prevalence of microvascular complications to be 17.7% [5]. Several factors have been identified as risk factors for microvascular complications in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%